2022
DOI: 10.7554/elife.80643
|View full text |Cite
|
Sign up to set email alerts
|

PLK4 drives centriole amplification and apical surface area expansion in multiciliated cells

Abstract: Multiciliated cells (MCCs) are terminally differentiated epithelia that assemble multiple motile cilia used to promote fluid flow. To template these cilia, MCCs dramatically expand their centriole content during a process known as centriole amplification. In cycling cells, the master regulator of centriole assembly Polo-like kinase 4 (PLK4) is essential for centriole duplication; however recent work has questioned the role of PLK4 in centriole assembly in MCCs. To address this discrepancy, we created genetical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Centriole biogenesis during multiciliate cell differentiation is accomplished through the same regulators that are required for centriole duplication during the cell cycle and Al Jord et al proved that proteins that control cell cycle progression are also essential to drive multiciliated cell differentiation (Al Jord et al, 2017). Very recently, it was suggested that PLK4 protein and its kinase activity are essential for centriole amplification in multiciliated cells (LoMastro et al, 2022). These results corroborate the idea that the initial stages of centriole assembly are conserved between cycling…”
Section: Previous Work Showed That Mcidas Forms a Stable Complex With...mentioning
confidence: 62%
“…Centriole biogenesis during multiciliate cell differentiation is accomplished through the same regulators that are required for centriole duplication during the cell cycle and Al Jord et al proved that proteins that control cell cycle progression are also essential to drive multiciliated cell differentiation (Al Jord et al, 2017). Very recently, it was suggested that PLK4 protein and its kinase activity are essential for centriole amplification in multiciliated cells (LoMastro et al, 2022). These results corroborate the idea that the initial stages of centriole assembly are conserved between cycling…”
Section: Previous Work Showed That Mcidas Forms a Stable Complex With...mentioning
confidence: 62%
“…Recent studies have revealed that PLK4 induced centrosome amplification is not only present in cancer cells but is also necessary for generating multiciliated cells [17, 44]. Previous research demonstrated that inducing PLK4 expression in human cells leads to centrosome rosettes (CRs) in the first cell cycle [19], followed by centrosome amplification in the second cell cycle [8].…”
Section: Discussionmentioning
confidence: 99%
“…Coverslips were mounted in ProLong TM Gold Antifade (ThermoFisher Scientific) or home-made mounting solution (23 % polyvinyl alcohol, 63 % glycerol and 0,02 % NaN3 in PBS). The following antibodies were used to perform immunofluorescence staining in murine cells: rabbit polyclonal α-CEP152 1:1000 (homemade, LoMastro et al ., 2022, 1:1000), goat polyclonal α-ɣ-Tubulin (homemade, Levine et al ., 2017, 1:1000), rabbit polyclonal α-CEP135 (homemade, LoMastro et al ., 2022, 1:1000), mouse α-ɣ-Tubulin (Sigma-Aldrich, 1:250); rabbit α-CP110 (Protein Tech, 12780-1-AP, 1:500), goat α-mouse IgG AF568 (Thermo Fisher, A11031, 1:1000), goat α-rabbit IgG AF488 (Thermo Fisher, A-11034, 1:1000).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were again washed 3 x with washing buffer.When Höchst 3342 (Sigma-Aldrich 23491-52) was used it was added in the last washing step.Coverslips were mounted in ProLong TM Gold Antifade (ThermoFisher Scientific) or home-made mounting solution (23 % polyvinyl alcohol, 63 % glycerol and 0,02 % NaN3 in PBS). The following antibodies were used to perform immunofluorescence staining in murine cells: rabbit polyclonal α-CEP152 1:1000(homemade, LoMastro et al, 2022(homemade, LoMastro et al, , 1:1000, goat polyclonal α-ɣ-Tubulin (homemade,Levine et al, 2017Levine et al, , 1:1000, rabbit polyclonal α-CEP135 (homemade,LoMastro et al, 2022LoMastro et al, , 1:1000, mouse α-ɣ-Tubulin (Sigma-Aldrich, 1:250); rabbit α-CP110 (Protein Tech, 12780-1-AP, 1:500), goat α -mouse IgG AF568 (Thermo Fisher, A11031, 1:1000), goat α -rabbit IgG AF488 (Thermo Fisher, A-11034, 1:1000).Thirty to fifty Z-stacks were acquired at room temperature on Zeiss Axiovert 200M microscope with an oil immersion objective (Ph3 Plan-Neofluar 100×/1.3 oil, 440481, Zeiss) using the acquisition software VisiView 4.1.0.3. Maximum stack projections of z-stacks were performed using the VisiView 4.1.0.3.…”
mentioning
confidence: 99%